Integration into the global scientific community (examplified by the reforms in the republic of China) - Vdovychenko Eugen (Borys Grinchenko Kyiv Metropolitan University, 2016)
The paper looks at the reasons and the process of reforming the system of higher education in the Republic of China under conditions of globalization and implementing market economy. It highlights the astonishing success of this country in the modernization of education for a short period of time. The study focuses on the importance of the government social support for the development of science and the prestigiousness of a lecturer's and a scientist's jobs. The paper specifies the main aspects of decentralization in Chinese higher education resulting in the formation of two levels of educational policies - governmental and regional. The governmental level deals with developing general principles and rules of regulating higher education; creating and implementing projects oriented towards achieving the world level of education. The regional level deals with solving the problem of training qualified workers aimed at enhancing the innovative economic development of the territories. The study stresses upon the measures taken by China's government to improve scientific activities at the universities. Great importance has been assigned to the development of students' analytical, critical, creative thinking, intellectual independence and the ability to gain, extract and transform information. The paper analyzes the policy of the eastern country regarding the reforms of managing personnel in the educational institutions. The closed appointment procedure has been eliminated - now it is public, announcing a vacancy and sharing the information about new vacant positions and applicants for them - for both academic and administrative staff. The programs promoting the creation of a competitive environment for the teaching staff have facilitated its continuous improvement. Now it is impossible to advance to higher positions only owing to one's experience and academic qualification.The conclusion can be drawn that if the government sets itself the task to take leading positions in the area of education, this task will not be solved without transformations in the economy and the system of government. .